What can be done? making the media and politics better/edited by John Lloyd and Jean Seaton - "Lloyd, John (ed.)" (Malden, 2006)
This book proposes a series of reforms that could improve the media and politics, and the interaction of the two, in Britain. * This book makes an important contribution to public debate in Britain about the relationship between the media and politics. * Contributors include academics, journalists and political commentators. * Topical issues covered include regulation, public service broadcasting, managing the news, and training journalists. * The focus is on Britain, but key commentators from America and Europe put the British problems into perspective.
Keywords: Mass media-Politicsl aspects